FORMING THE MODEL OF EFFICIENCY ESTIMATION OF TRANSACTIONAL COSTS IN EDUCATIONAL SPHERE - L. V. Vorontsova (Russian Journal of Economics and Law)
Objective: To elaborate the tools of transactional costs management in educational sphere in Russia. Methods: Institutional, cost and systemic approaches are used, as well as project management method. Results: The space-time classification of transactional costs of organization is used, the influence of institutional environment on transactional costs forming is taken into account; the model is elaborated for estimating the efficiency of management of the main groups of transactional costs in the educational sphere in Russia. Scientific novelty: Benchmarking is viewed as a tool for managing transactional costs in the educational sphere. New forms of benchmarking are proposed for management in the sphere of education – benchmarkingof institutions and integration benchmarking, consequently, the previously proposed classifications of benchmarking are broadened by the object of comparing and by the partner status. For the first time the model is elaborated for estimating the efficiency of management of the main groups of transactional costs in the educational sphere in Russia. Practical value: The model is formed for estimating the efficiency of management of the main groups of transactional costs in the educational sphere in Russia, which is aimed at being used by the practical managers in the process of educational establishments’ management, as well as educational sphere as a whole.